Pendidikan Pancasila Sebagai Upaya Mempertahankan Identitas Nasional Dan Hak Asasi Manusia Di Era Globalisasi - Wardah Nuranisa; Aprizia Perenial Asla Wahyudi; Maulia Depriya Kembara (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
A balanced and sustainable understanding of national identity, human rights, and globalization is key to shaping an inclusive and just society in an era of global dynamics. This article aims to explore the role of Pancasila education in maintaining national identity and human rights in the era of globalization. This article examines the science with qualitative methods with in-depth-interview data collection techniques by analyzing literature and policies related to Pancasila education and its impact on national identity and human rights. The results show that Pancasila education provides a strong foundation for the community in understanding national values and human rights, as well as forming an attitude that is inclusive and appreciates diversity in the era of globalization. This article is important to strengthen the understanding of the urgency of Pancasila education as the main fortress in maintaining national identity and human rights amid the complex challenges of globalization.